Penciptaan Komunikasi Visual Perancangan Program Edutainment “Seri Aktivitas Alam: Gunung Meletus” - Andreas James Darmawan; Dyah Gayatri Putri (Bina Nusantara University, 2015)
This research is the continuation of previous research. The research is included in the creation of visual communication solutions on how a process of visual communication strategy can contribute a persuasive invitation. Research aims to expose the solution in the realm of visual communication. The research applied qualitative method. It began with the development of communicators becoming a mascot, continued on the delivery of messages through the comics, and invited children as audience target for design experience with game and gimmick. Result of the research is the visual design, as well as including the process of visual communication creation. As a conclusion, creating a visual communication solution could be carried out by the same method, similar matching scope, as well as the contents adjusted with new needs.